Unlocking Strength: The Powerful Impact of Ashwagandha (Withania somnifera) Supplementation on Resistance Training - Sikorski, Piotr; Malinowski, Piotr; Kopczyńska, Urszula; Kopczyński, Cezary; Gurdak, Kinga; Dydyk, Martyna; Dyrek, Martyna; Błaszczak, Ewa; Wójcik, Jakub; Partyka, Aleksandra (Journal of Education, Health and Sport, 2024)
Withania somnifera, commonly known as ashwagandha, has gained popularity in recent years among individuals interested in healthy lifestyles, natural medicine, and sports. This review aims to summarize the current knowledge regarding the effects of ashwagandha supplementation on various aspects of physical performance, particularly in the context of resistance training. Studies have shown that ashwagandha can positively impact muscle strength, with significant increase of muscle force and power output. Additionally, it has demonstrated potential in modulating body composition, with reduction of body fat percentage noted in certain populations. However, results of studies on ashwagandha’s effect on muscle size remain inconclusive and may depend on various factors such as training status and individual responses. In terms of endurance, ashwagandha supplementation has been associated with improvement in maximal oxygen uptake, indicating enhanced aerobic capacity and delayed exhaustion during endurance activities. Furthermore, ashwagandha was shown to aid muscle recovery by reducing exercise-induced muscle damage and inflammatory response, potentially accelerating the muscle regeneration process. Ashwagandha may also influence hormone levels, such as testosterone and cortisol, with potential implications for muscle growth and recovery. However, further research is needed to fully understand the mechanisms underlying these effects. Overall, ashwagandha supplementation appears to hold promise for enhancing physical performance and overall well-being. Further research is needed to elucidate optimal dosages, long-term safety, and potential interactions with other supplements or medications.